Mannose receptor targeted bioadhesive chitosan nanoparticles of clofazimine for effective therapy of tuberculosis - Pawde, D.M.; Viswanadh, M.K.; Mehata, A.K.; Sonkar, R.; Narendra; Poddar, S.; Burande, A.S.; Jha, A.; Vajanthri, K.Y.; Mahto, S.K.; Azger Dustakeer, V.N.; Muthu, M.S. (Elsevier B.V., 2020)
Drug-resistant tuberculosis (TB) is one of the most lethal diseases, and it is imperative to exploit an advanced drug formulation for its effective treatment. This work aims to develop a mannose receptor-targeted bioadhesive chitosan nanoparticles for effective drug-resistant tuberculosis treatment. The clofazimine loaded chitosan nanoparticles were formulated; their size, charge, polydispersity (PDI), surface morphology, entrapment efficiency (EE) and in-vitro release pattern were established. Also, cellular uptake study on C2C12 cell lines and anti-mycobacterial activity against H37Rv (a standard strain of Mycobacterium tuberculosis) were evaluated. The particle sizes of formulated chitosan nanoparticles were in the range of 132–184 nm and EE was also found to be between 73 and 95%. The functionalization of bioadhesive chitosan nanoparticles with mannose was confirmed by infrared spectroscopy (FTIR). The uptake studies on the C2C12 cell lines showed that mannosylated nanoparticles were more efficiently internalized when compared to non-targeted nanoparticles. Further, luciferase reporter phage (LRP) assay against H37Rv strain showed that clofazimine nanoparticles were found to be 49.5 times superior in terms of inhibition and anti-mycobacterial activity than free clofazimine. This excellent activity might be attributed to enhanced drug delivery with a promising bioadhesion property of chitosan-based nanoparticles. © 2020
Keywords: Chitosan; Clofazimine; Mannose receptor; Nanoparticles; Tuberculosis